Oral Immune Priming Treatment Alters Microbiome Composition in the Red Flour Beetle Tribolium castaneum - Korša, Ana; Lo, Lai Ka; Gandhi, Shrey; Bang, Corinna; Kurtz, Joachim (Frontiers in Microbiology, 2022)
It is now well-established that the microbiome is relevant for many of an organism’s properties and that its composition reacts dynamically to various conditions. The microbiome interacts with host immunity and can play important roles in the defenses against pathogens. In invertebrates, immune priming, i.e., improved survival upon secondary exposure to a previously encountered pathogen, can be dependent upon the presence of the gut microbiome. However, it is currently unknown whether the microbiome changes upon priming treatment. We here addressed this question in a well-established model for immune priming, the red flour beetle Tribolium castaneum exposed to the entomopathogenic bacterium Bacillus thuringiensis (Bt). After priming treatments, the microbiota composition of beetle larvae was assessed by deep sequencing of the V1-V2 region of the bacterial 16S rRNA gene. We compared the effect of two established routes of priming treatments in this system: injection priming with heat-killed Bt and oral priming via ingestion of filtered sterilized bacterial spore culture supernatants. For oral priming, we used several strains of Bt known to vary in their ability to induce priming. Our study revealed changes in microbiome composition following the oral priming treatment with two different strains of Bt, only one of which (Bt tenebrionis, Btt) is known to lead to improved survival. In contrast, injection priming treatment with the same bacterial strain did not result in microbiome changes. Combined with previous results indicating that oral priming with Btt depends on the larval microbiome, this suggests that certain members of the microbiome could be involved in forming an oral priming response in the red flour beetle.